Pelatihan Berfikir Positif untuk Meningkatkan Self-Esteem pada Remaja Yatim Piatu di Yogyakarta - Hanggari Deasy; Kamsih Astuti; Kondang Budiyani (Jurnal Psikologi, 2020)
The aim of this research is to test the effectivennes the effects of positif thinking training in self-esteem of teen orphanage woman ‘X’ Yogyakarta. Subjects were 12 adolescents divided into 6 subjects of the experimental group and 6 subjects of the control group with low and medium self-esteem categories. Self-esteem category obtained from score scale Coopersmith Self Esteem Inventory (CSEI) from Coopersmith (1967) adapted and modified by the researchers. The research design used pre-post control group design with data analysis technique used Mann-Whitney test and Wilcoxon test. The Mann-Whitney test was used to see the difference in scores in the experimental and control groups. The result of data analysis with Mann-Whitney test showed that there was no significant difference of self-esteem in the experimental group after being treated with self-esteem control group without being treated (p = 0,746> 0,05). The result of data analysis with Wilcoxon test showed that there was a significant difference of self-esteem in experimental group before and after treatment (p = 0,027 <0,05).The aim of this research is to test the effectivennes the effects of positif thinking training inself-esteem of teen orphanage woman ‘X’ Yogyakarta. Subjects were 12 adolescentsdivided into 6subjects of the experimental group and 6 subjects of the control group with lowand medium self-esteem categories. Self-esteem category obtained from score scaleCoopersmithSelf Esteem Inventory (CSEI) from Coopersmith (1967) adapted and modifiedby theresearchers. The research design used pre-post control group design with dataanalysis technique used Mann-Whitney test and Wilcoxon test. The Mann-Whitney test wasused to see the difference in scores in the experimental and control groups. The result ofdata analysis with Mann-Whitney test showed that there was no significant difference of selfesteemintheexperimentalgroupafterbeingtreatedwithself-esteemcontrolgroupwithoutbeingtreated(p=0,746>0,05).TheresultofdataanalysiswithWilcoxontestshowedthattherewasasignificantdifferenceofself-esteeminexperimentalgroupbeforeandaftertreatment(p=0,027<0,05).